Key to the species of the genus Scleria (Cyperaceae) in Costa Rica based on the morphology of achenes - Espinoza Morales, Lindsay Patricia (2016)
We described the achenes of 21 species of the genus Scleria reported in Costa Rica using 16 morphological characters and developed a key based only on achene characteristics. Specimens deposited in herbaria in Costa Rica were analyzed. We observed the achenes using a stereoscope and light microscope and took digital images that were used to measure the achenes. Besides, the achenes were observed using a Scanning Electron Microscope. A cluster analysis using achene characteristics was performed in order to know which species are morphologically similar. The intra-specific variation of the characteristics analyzed in the achenes studied is very small for all the species. Using characteristics of the achene, we could differentiate species among four of the five traditional sections of the genus used to classify the species: Hypoporum, Ophryoscleria, Schizolepis and Scleria. The key allows differentiating among 21 species of the genus Scleria previously reported in Costa Rica using only achenes. Besides the key, we prepared an illustrative guide for the genus using pictures taken with SEM and a stereoscope. The descriptions offer better information about the species that grow in Costa Rica.